Ornamentasi Seni Pertunjukan Etu Nagekeo Sebagai Bentuk Ekspresi Kerakyatan (Lembaga Pengembangan Kinerja Dosen, 2025)
Abstract. The diversity of popular expressions in performing arts is a tangible form of noble cultural heritage in various regions of Indonesia. The ornamentation of performing arts as a medium of expression has produced esteemed cultural rituals that deserve preservation across generations. The ethics of performing art ornamentation in each region carry distinctive characteristics, values, and norms, including the Etu Ritual in Nagekeo, East Nusa Tenggara. Etu, also known as the traditional boxing performance, represents a complex repertoire of movements, vocabulary, music, and religious entities. This study employs a qualitative ethnographic method with a semiotic approach to examine the structure, expression, and meaning of the Etu performance in Nagekeo. Research data sources are divided into two categories: primary and secondary. Four techniques of data collection are applied, namely participatory observation, in-depth interviews, documentation, and literature study. Data processing is conducted in three phases: data condensation, data presentation, and conclusion drawing. The objectives of this study are as follows: (1) to examine the history, development, and structure of performing arts within the Etu ritual of Nagekeo; (2) to analyze the ornamentation of performing arts in the Etu ritual of Nagekeo; and (3) to analyze the expression of popular culture within the Etu ritual of Nagekeo as part of the nation’s heritage.